Hidden tactics: Deposit agreement in debt contracts - Siti Novriannisya; Andi Tenri Famauri; Muhammad Basri; Jamal Aslam; Mohd Shahril Nizam MD Radzi (Universitas Ahmad Dahlan, 2025)
Introduction to the Problem: The deposit agreement in the debt agreement, as stated in the receipt, strategically influences the power dynamics between the creditor and the debtor. Often, the practice of such contracts is used to disguise the true intent. The deposit agreement provision behind the debt agreement ensures greater control over the repayment process. In the event of default, the creditor uses the receipt with the deposit clause to report the debtor for embezzlement. Purpose/Study Objectives: This paper analyses the provisions of debt agreements made in deposit receipts to find the best solution for fulfilling a balanced contractual relationship. Design/Methodology/Approach: This research employs a normative juridical approach, focusing on literature reviews, legislative regulations with specific details, and analytical descriptive research. Findings: This research shows that debt and deposit agreements contained in the deed of release of rights are valid and binding for the parties involved as long as no party denies them. However, upon closer examination of the agreement's intent and purpose, it becomes apparent that the agreement can be fabricated and contain invalid reasons. Although the principle of freedom of contract applies to the agreement, it does not mean that you can do it as freely as possible. Criminalizing someone for breaching a contract is not an appropriate course of action. It should be a concern for law enforcement officers unless there is strong evidence that embezzlement or fraud has occurred. Paper Type: Research Article